2004
DOI: 10.1093/jn/134.9.2336
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Cash Transfers Are Associated with a Small Reduction in the Rate of Weight Gain of Preschool Children in Northeast Brazil

Abstract: Programs providing cash transfers to poor families, conditioned upon uptake of preventive health services, are common in Latin America. Because of the consistent association between undernutrition and poverty, and the role of health services in providing growth promotion, these programs are supposed to improve children's growth. The impact of such a program was assessed in 4 municipalities in northeast Brazil by comparing 1387 children under 7 y of age from program beneficiary households with 502 matched nonbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
2
18

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 8 publications
3
98
2
18
Order By: Relevance
“…A similar result was found by an assessment of the Bangladesh Integrated Nutrition Project (PINB) which also showed that the project had no significant impact on wasting in children 22 . However, our results differ from those found by an assessment of the Bolsa Familia program in Brazil which found that the intervention led to an improvement in nutritional status among participating children 23 . Our results also differ from the findings of a study conducted by the ICBF of the HCB program.…”
Section: Variablecontrasting
confidence: 99%
“…A similar result was found by an assessment of the Bangladesh Integrated Nutrition Project (PINB) which also showed that the project had no significant impact on wasting in children 22 . However, our results differ from those found by an assessment of the Bolsa Familia program in Brazil which found that the intervention led to an improvement in nutritional status among participating children 23 . Our results also differ from the findings of a study conducted by the ICBF of the HCB program.…”
Section: Variablecontrasting
confidence: 99%
“…For example, a range of econometric methods has recently been applied to study the outcomes of the Conditional Cash Transfer initiative (CCT), variants of which operate in Mexico, Brazil and many other countries (Gertler, 2004;Morris et al, 2004;Attanasio et al, 2005). Families enrolled in CCT programmes receive cash in exchange for complying with certain conditions: preventative health requirements, nutrition supplements, enrollment in school and monitoring.…”
Section: Assessing Causalitymentioning
confidence: 99%
“…Amongst the few papers that can be found on BF's effects, many have focused on economic effects related to poverty, income inequality, and consumption (Soares et al, 2006;Osório et al, 2007;Resende and Oliveira, 2007;Tavares, 2008;Lignani et al, 2011), and more recently on adults' participation in the labour market (Tavares, 2008;Foguel and Barros, 2010). Studies of the impacts of BF on child development, health, and nutritional status of children can also be found in the literature (Morris et al, 2004;Castiñeira, Nunes and Rungo, 2009;Reis, 2010;Lima, Rabito and Dias, 2011;Paes-Sousa, Santos and Miazak, 2011;Piperata et al, 2011). As to effects on education and child labour, although there are very few studies to date, these were, in fact, the primarily areas of interest at the time of the first CCT experiences, when education was the heart of the programmes.…”
Section: The Educational Impacts Of Bolsa Família: a Brief Reviewmentioning
confidence: 99%